1992
DOI: 10.1159/000238946
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Alterations Responsible for Combined Quinolone and β-Lactam Resistance in <i>Pseudomonas aeruginosa</i>

Abstract: Resistant variants of three clinical Pseudomonas aeruginosa isolates were obtained in the presence of aztreonam. The variants exhibited a four- to eightfold increase in the minimal inhibitory concentrations to β-lactam antibiotics (except imipenem) to quinolones, such as norfloxacin and fleroxacin, chloramphenicol and tetracycline, but not to gentamicin and polymyxin B. β-Lactamase production was barely detectable in both wild-type strains and the resistant clones. Only ampicillin, cefoxitin and imipenem incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Such multidrug resistance has been attributed mostly to either the decreased permeability of the outer membrane, in which the compositions of porin proteins and LPS are of importance, or the increased activity of efflux pumps, or both (Leying et al 1992;Nikaido 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Such multidrug resistance has been attributed mostly to either the decreased permeability of the outer membrane, in which the compositions of porin proteins and LPS are of importance, or the increased activity of efflux pumps, or both (Leying et al 1992;Nikaido 1994).…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSION In members of the family Enterobacteriaceae, resistance to quinolones is often due to a reduction in drug permeation associated with a decrease in OmpF, the principal porin protein (4,5,15). On the other hand, many mechanisms of resistance have been reported for P. aeruginosa (1,3,6,10,19). Yoshida et al (19) studied the proportion of gyr mutations in quinolone-resistant clinical isolates of P. aeruginosa and found that the gyrA mutation conferred various degrees of quinolone resistance on susceptible strains.…”
Section: Methodsmentioning
confidence: 99%
“…These antipseudomonal penam resistances may be caused by the interplay between efflux and influx proteins, and/or by qualitative and quantitative alterations in lipopolysaccharides. 7,8 The 23 piperacillin-resistant isolates were widely distributed in the hospital wards, and were made up of O-antigens A (isolation rate, 9%), B (17%), C (13%), E (53%), G (4%), and non-typable (4%). Three of the 4 isolates producing OXA-4 -lactamase, isolates 2043, 2103 and 2109, were from the urine of patients hospitalized in the urology and kidney wards, and the periods of hospitalization overlapped.…”
Section: Resultsmentioning
confidence: 99%